Deciphering the Structure–Immunomodulatory Function Relationships of Homopolysaccharides. - Hu, Gege; Yang, Bingyu; Song, Han; Zeng, Yuehan; Zhang, Zhuoting; Li, Yuwen; Zhang, Jian; Wang, Fenghuan (Nutrients, 2026)
Natural homopolysaccharides (HoPSs), composed of a single monosaccharide type, are increasingly recognized as bioactive macronutrients with broad relevance to nutrition and health. This review summarizes the extraction, structural characterization, and structure-immunomodulatory activity relationships of HoPSs. Drawing on a comprehensive synthesis of existing studies, we integrate current knowledge into a unified hierarchical framework of HoPS structure–function relationships. This framework organizes the literature into three hierarchical levels, including primary structural recognition, mid-level regulatory mechanisms, and functional refinement, while integrating key determinants such as molecular weight, glycosidic linkages, chain conformation, branching, and chemical modifications. By bridging structural glycomics and nutritional immunology, this framework synthesizes current evidence and provides a structured reference for future investigations. HoPSs exert well-established anti-infection and anti-inflammatory effects, alongside important nutritional and metabolic benefits. These outcomes are supported by evidence from cellular receptor signaling (e.g., TLRs, Dectin-1; NF-κB, MAPK pathways), gut microbiota remodeling, and metabolite network interactions. Finally, we discuss current research gaps, particularly in fine structural analysis and multidimensional mechanistic studies, and propose future directions based on precise structural elucidation, multidimensional structure–activity relationship modeling, and interdisciplinary integration. This review aims to bridge structural glycomics with human nutritional immunology, providing a theoretical basis for the structural optimization, immune activity enhancement, and functional food development of natural HoPSs to promote their industrial application in medicine, nutrition, and health.